Effects of body condition scores and fat depots on gene expression of fatty acid synthase in horses - Doran, Lynn A., author; Yemm, R., author; Dickinson, C. E., author; Hossner, Kim L., author (Colorado State University. Libraries, 2005)
The current study was designed to examine the expression of fatty acid synthase (FAS) genes in horse adipose tissue. Subcutaneous and visceral fat samples were collected from Quarter horses with obese or normal body condition scores and four fat samples were taken from clinical admission horses that were diagnosed with Cushing's disease at the C.S.U. Veterinary Teaching Hospital. Total RNA was isolated from the fat samples and analyzed by ribonuclease protection assay. A nonisotopic ribonucleic probe for fatty acid synthase (FAS) mRNA was constructed from sheep RNA and was utilized for analysis. The results from the ribonuclease protection assays on the four horses with both visceral and subcutaneous fat samples were analyzed to determine the effects of body condition scores and fat depots on the level of adipose tissue FAS mRNA expression. No difference in FAS gene expression was seen in horses with normal (BCS=3) or obese (BCS=5) body condition scores. The expression of FAS in visceral versus subcutaneous fat depots was numerically but not statistically significant. The data suggest that an ovine probe for FAS mRNA can be effectively used in horses. Although no differences were observed between fat depots, body condition score or Cushing's horses, use of larger sample numbers may provide significant results.
Analysis of ACC, FAS, LPL, PPARg, and SCD expression in horses
Keywords: Fatty acids; Adipose tissues; Gene expression; Horses -- Genetics